MENINGKATKAN KEPERCAYAAN DIRI ANAK MELALUI “REWARD ASYIK” DI TK NEGERI PEDESAAN - Ayu Vera Dewi; Sri Watini (LPPM Universitas Bina Bangsa, 2022)
Self-confidence is an important thing for early childhood to have, because having confidence will grow courage and increase children's enthusiasm to learn. Confidence is the ability of children to express feelings, be able to interact with others and dare to face life in the environment. At the Rural State Kindergarten, Walantaka District, Serang City, there are still some children who are not confident, such as lack of communication, not daring to express their feelings or opinions, not daring to answer the teacher's questions, being afraid and embarrassed to come to the front of the class. This research was conducted to increase the self-confidence of children aged 4-6 years in Rural State Kindergarten, Walantaka District, Serang City by using the